(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Cardiovascular diseases (CVD) remain one of the leading causes of mortality worldwide. According to global epidemiological data, millions of people die each year as a result of cardiovascular pathologies. In recent years, it has been emphasized that not only traditional risk factors (smoking, obesity, physical inactivity, and unhealthy diet), but also atmospheric and cosmic environmental factors may play an important role in the development of these diseases.